Crossing numbers of Cartesian product of path with certain graphs on six vertices - Gayathri S.; Bharati R.; Stas M.; Petrillova J. (Utilitas Mathematica, 2020)
In this paper we determine the crossing numbers of Cartesian product of path with certain graphs on six vertices. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.